Art games e educação em contexto híbrido e multimodal : aprendizagem imersiva em movimento - Lima, Tatiana Araujo de (Universidade do Vale do Rio dos Sinos, 2019)
Art Game Experience emerged as a practice in which exclusive art game was developed through the HP Reveal application, in which three groups played through tracks in the form of QR Codes scattered and affixed along the UNISINOS Campus in São Leopoldo, Brazil. We used knowledge about the focus groups together with the cartographic method of research-intervention, based on Kastrup (2007), Passos, Kastrup and Escóssia (2009) and Passos, Kastrup and Tedesco (2014) for the main analyzes of this Dissertation, favoring the understanding of the process established by the groups and their trajectories along the developed tracks. There was the design of some digital trails such as Blog posts: Immersion... live exceeds all understanding, and photographs of the clues published in Instagram @artgameexperience. These publications were a strategy for all those who were in the Campus both to take notice of Art Game Experience through the Blog posts, and to participate following the instructions posted along the QR Codes tracks, exclusively developed for this Dissertation, with material in photos and videos of the author. They are part of the context of the processes generated along the path experienced by the groups, problematizations regarding mobility, pervasiveness, ubiquity, connectivity, and, especially, hybridism and multimodality. From the contexts in which these aspects are interrelated, the main ones - interactivity, immersion, subjective capture, agency and transformation - stand out the issues of analysis of this Dissertation. It also highlights as questions of analysis: a) the contact and the resignification of the Jesuit culture present in some of the developed tracks; and b) the production of knowledge, since in the cartographic method of research-intervention, the understanding of knowledge experiences pervades the group processes, as well as the researcher, who acts as a cartographer and facilitator of group experiences. The participant groups were transformed by the process of playing the art game, and their degrees of involvement exceeded expectations, so that the subjective capture was quite intense, to the point of losing completely the notion of passage of time. Other relevant aspects such as interactivity and immersion were highlighted in an intense way in the group experiences, besides the transformations reported by its members when involved in the game throughout the group processes. Art Game Experience elicited reflections about the transforming role that the contact with the playful and the nature can exert subjectively, and of how much the hybrid and the multimodal intertwine in this process. In relation to the hybrid, we have the concomitant presence both relative to the geographical and digital spaces, in which the participants of the different groups take ownership in the different crossings that they develop; as well as hybridism related to technologies, in which analog and digital are mixed both with the development of the art game created, and with regard to the use of smartphones over time. To the teaching and learning processes contextually, questions about pedagogical mediation and digital technological appropriation, as well as references to mobile learning, pervasive learning, ubiquitous learning and immersive learning, are being questioned.
Keywords: Art game; Arte digital; Educação digital; Hibridismo; Multimodalidade; Art game; Digital art; Digital education; Hybridism; Multimodality; ACCNPQ::Ciências Humanas::Educação